Marketing Mix on Customer Satisfaction at the Tax Consulting Office Dr. Sudarno, S.Pd., M.M., BKP and Colleagues Pekanbaru - Suyono, Suyono; Lestari, Dania Ayu; Rusilawati, Ermina; Kudri, Wan Muhamad; Renaldo, Nicholas (Journal of Applied Business and Technology, 2023)
Research is to identify and analyze the effect of the marketing mix on customer satisfaction partially and simultaneously at the tax consultant office of Dr. Sudarno, S.Pd., M.M., BKP and partners Pekanbaru. The research sample was all clients of the tax consultant office of Dr. Sudarno, S.Pd., M.M., BKP and partners in Pekanbaru city as many as 86 clients consisting of 44 corporate income tax and 42 income tax clients. Determination of the sample using the census method or saturated sampling. The data analysis technique used is multiple linear regression with SPSS Windows 19. The independent variables are product, price, place, promotion, people, process, and physical evidence while the dependent variable is customer satisfaction. The results showed that product, promotion, people, process, and physical evidence had a significant positive effect both partially and simultaneously on customer satisfaction. However, the results of the study also show that the price variable has a significant negative effect on customer satisfaction and the location variable has an insignificant negative either partially or simultaneously on customer satisfaction at the tax consultant office Dr. Sudarno, S.Pd., M.M., BKP and colleagues Pekanbaru.